Investigation of dielectric properties of PEGMEA/PEGDA nanocomposites containing in-situ photochemically prepared ?-Fe2O3 nanocrystals - Kirtay, Hicret; Yakut, Sahin; Deger, Deniz; Ulutas, Kemal; Arsu, Nergis (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
Photopolymerization of PEGMEA/PEGDA monomer mixture consisting of FeCl3.6H2O metallic salt was performed using a Type I photoinitiator, namely 2-Hydroxy-4 '-(2-hydroxyethyl)-2-methyl propane (Irgacure 2959). Herein, we report the easy and one-step in-situ synthesis method of a rare e-Fe2O3 polymorph in a polymer matrix with different concentrations of Fe3+ salt. Thermal gravimetric analyses of the nanocomposites indicate an increase of char yield depending on both the synthesized nanoparticle concentration and good distribution of Nps. SEM images are also proof of formation of e-Fe2O3 Nps in polymer matrix. The obtained results indicate 4 and 20%w/w Fe3+ salt loading in the formulations resulted in higher char yield. Dielectric spectroscopy analysis and calculated glass transition temperatures show that there may be a critical ratio between 4 and 8% in the A1 and A2 samples, in comparison with the sample A3 which is the nanocomposite with 20% e-Fe2O3 Nps. A3 probably has excess free charges contributing to additional conduction.
Keywords: Nanocomposite; Photopolymerization; Glass transition temperature; Dielectric spectroscopy; ?-Fe2O3nanocrystals; IRON-OXIDE NANOPARTICLES; MAGNETIC-PROPERTIES; AC CONDUCTIVITY; POLYMER MATRIX; THIOXANTHONE; PHOTOINITIATORS; RELAXATION; FILMS; Materials Science